2013
DOI: 10.1111/1756-185x.12209
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid arthritis disease activity and vitamin D deficiency in an Asian resident population

Abstract: We highlight the importance of skin exposure to sunlight in a conservative dressing culture. No association was observed between vitamin D and disease activity. However, the high prevalence of vitamin D deficiency may negatively impact on bone health of these patients in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 17 publications
0
6
1
Order By: Relevance
“…[21][22][23] Several human studies have shown an inverse relationship between vitamin D and several chronic conditions associated with inflammation. [24][25][26][27] In the eye, vitamin D may prevent AMD progression via its antiinflammatory and antiangiogenic properties. 28 However, epidemiologic studies on the relationship between vitamin D and AMD have been limited, and the results are inconsistent.…”
mentioning
confidence: 99%
“…[21][22][23] Several human studies have shown an inverse relationship between vitamin D and several chronic conditions associated with inflammation. [24][25][26][27] In the eye, vitamin D may prevent AMD progression via its antiinflammatory and antiangiogenic properties. 28 However, epidemiologic studies on the relationship between vitamin D and AMD have been limited, and the results are inconsistent.…”
mentioning
confidence: 99%
“…In addition, there was no significant relationship between duration of illness and serum 25 (OH) vitamin D level [14]. In a study with 35 patients in the United Arab Emirates, there was no significant correlation between serum vitamin D levels and disease activity score (DAS28) or HAQ scores [15]. In another study with patients with RA, a moderately significant negative correlation was found between serum 25 (OH) vitamin D level in active disease, pain, and number of sensitive joints and DAS28, but no significant correlation was found between parameters in the remission group [16].…”
Section: Discussionmentioning
confidence: 95%
“…In a study performed by Quraishi et al . in RA patients from Dubai, mainly originating from the Indian subcontinent and of Arab origin, no association was found between disease activity and vitamin D levels; this finding may be explained by the fact that the disease was well controlled with DMARDs, mainly methotrexate …”
Section: A Role In Autoimmune Diseases Such As Ramentioning
confidence: 89%